Evaluation of the impact of Bus Rapid Transit on air pollution in Mexico City. (April 2018) - Bel, Germà; Holst, Maximilian
Abstract: Mexico City's bus rapid transit (BRT) network, Metrobus, was introduced in an attempt to reduce congestion, increase city transport efficiency and cut air polluting emissions. In June 2005, the first BRT line in the metropolitan area began service. We use the differences-in-differences technique to make the first quantitative assessment of the policy impact of a BRT system on air polluting emissions. The air pollutants considered are carbon monoxide (CO), nitrogen oxides (NOX ), particulate matter of less than 10 μm (PM10 ), and sulfur dioxide (SO2 ). The ex-post analysis uses real field data from air quality monitoring stations for periods before and after BRT implementation. Results show that BRT constitutes an effective environmental policy, reducing emissions of CO, NOX, and PM10 . Highlights: Bus Rapid Transit was introduced in Mexico to alleviate urban congestion and pollution. We use field data to evaluate the impact of Bus Rapid Transit on air pollution. Differences-in-differences show significant reductions in CO, NOX, and PM10 . Introduction of Bus Rapid Transit helped to significantly reduce air pollution in Mexico City.